Rancang Bangun Pengingat Pembersihan Limbah Greshtrep Otomatis Berbasis Arduino - Asni Tafrikhatin; Yulia Bherlinda; Ajeng Tiara Wulandari; Angga Azfananda (Politeknik Piksi Ganesha Indonesia, 2022)
Currently, the cleaning or cleaning schedule for greasetrap is done manually so that human errors can occur such as forgetfulness which can affect the final outcome of waste disposal. The purpose of this tool is to make it easier for the crew in scheduling greasetrap cleaning so as to minimize the occurrence of human errors. Based on the description above, the researchers made an automatic grease trap cleaning reminder alarm with a turbidity sensor based on the Atmega 328 microcontroller. The method of making this product uses Research and Development. The R&D stages include: collecting data, creating product designs, building products, and testing products. This greasetrap cleaning alarm can be utilized as an automatic control system. The components of this tool include: turbidity sensor, ATmega 328 microcontroller, servo motor, LED, buzzer. The way this tool works with the turbidity sensor as a detection sensor for objects then the ATmega 328 microcontroller is used as a processing tool for this reminder alarm system, the output of this system is a servo motor as a greasetrap filter puller, LED and buzzer as notification.